Initiative for development of a unified Baltic legal and regulatory framework for corporate bond issuance - Cakure, Agne (Riga Graduate School of Law, 2020)
This bachelor thesis aims to assess a unified legal and regulatory framework for pan-Baltic corporate bond issuance, as such or similar initiative has not been introduced in the Baltic state level. This research evaluates the proposed initiative by providing a theoretical insight in corporate bond types, issuance and legal and regulatory framework formation by reviewing the connections and influence of the relevant legislative levels, with the focus of European Union. Moreover, it provides reasoning for launching such initiative, by analysing the present legal and regulatory framework applying to corporate bond issues, significantly influenced by the Capital Market Union initiative developed by the European Commission, as well as the Baltic level developments in capital markets. By assessing the elements of current legal and regulatory framework applying to corporate bond issues in the Baltics, more specifically, the information disclosure requirements, including the Regulation (EU) 2017/1129 (Prospectus Regulation), and bondholders as creditors in case of default of the issuer, the research establishes the foundation for evaluation of the proposed initiative. This research results in recommendations presented, directed towards Baltic state national governments and regulators, as well as Baltic infrastructure providers, in order to recommend the consideration of the proposal of an initiative for development of a unified Baltic legal and regulatory framework for corporate bond issuance
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Commercial and company law; Baltic states; Bonds